What Teacher Collaboration Looks Like - Vincente, Joseph (American Educator, 2017)
In this article, Joseph Vincente, an assistant principal and math and instructional coach at East Side Community High School in New York City, describes East Side's collaborative structures as well as the norms and conditions that support them. Collaboration underpins how the teachers at East Side structure and conduct most of their work, how they serve students, and how they learn and grow as professionals. The author discusses the following collaborative structures: (1) grade teams; (2) vertical teams; (3) professional learning groups; and (4) roundtables.
Keywords: Collegiality; Communities of Practice; Group Discussion; High School Students; High Schools; Secondary School Teachers; Teacher Collaboration; Teamwork